Celebrating differences : the work of bptw partnership (London : Black Dog Architecture, 2009)
Innovation in design, construction, planning and sustainability have established bptw's reputation within the residential, regeneration, special needs, education, health care and mixed-use sectors. The work of bptw: Celebrating Differences explores bptw's approach providing an in-depth insight into the practice's philosophy and working methods. Based in Greenwich, UK, for the last fourteen years the projects undertaken by bptw partnership are models of socially and environmentally conscious design. Renowned for its work with a range of clients, including private developers, housing associations, local authorities and community groups, bptw's Celebrating Differences presents the work of the practice in all its diversity. Interspersed throughout Celebrating Differences are case studies of projects including award-winning public housing developments such as the Pepys Estate, commercial buildings and bptw's masterplanning of housing projects and mixed-use tenures. With a host of awards affirming their success, including Best Architectural Practice from Building Awards in 2005, this volume is a timely look at the beliefs and attitudes that make bptw one of the more innovative architectural practices working within the housing sector today.
Keywords: Architectural firms -- Great Britain